Consequences of deviation from the curve radius in the high jump approach - Becker, J.; Kerin, D.; Chou, L.-S. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to examine how well elite high jump athletes run the curved portion of the approach and how deviation from the curve affects parameters related to jump performance. The participants were elite men and women high jumpers competing in the 2012 USA Track & Field Olympic Trials. Based on reconstructed coordinates, constant radius curves were fitted to the approach of the jumpers and deviation from the curve on each step was analysed. All athletes demonstrated some degree of deviation from the curve, with the 8th and penultimate steps being the most common sites of maximum deviation. There were significant beneficial relationships between maximum deviation from the curve and the height of the center of mass at plant and vertical velocity at takeoff. However, there were significant detrimental relationships between maximum curve deviation and change in inward lean during the takeoff and distance travelled down the bar. Overall, the results of this study suggest deviation from the curve radius may be mechanisms to help jumpers produce increased vertical velocity at takeoff but it comes at the price of negatively affecting bar clearance.